Improving Early Reading Skills in Elementary Students with the Structural Analytic Synthetic Method Based on Flashcards - Erlin, Erlin; Saptono, Bambang (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
The low early reading skills of first-grade students at Rangkang 09 Elementary School, Bengkayang Regency, is a problem that requires immediate attention. Students' limited ability to recognize letters, form words, and understand simple texts hinders the development of their basic literacy. This study aims to improve early reading skills through the SAS (Structural Analytic Synthetic) method, which helps students understand both analytically and synthetically word structures. Using the classroom action research model by Kemmis & Taggart, implemented over two cycles, the study involved 30 first-grade students as participants. Data were collected through observations, reading tests, and documentation and analyzed using descriptive quantitative methods to measure changes in student reading ability. The finding shows that there is a significant improvement in student performance after two cycles which suggest that the SAS method is viable for early literacy instruction. Furthermore, the study underscores the role of teacher proficiency in the successful implementation of this method, emphasizing the need for targeted teacher training to maximize educational outcomes. This research contributes to the body of knowledge by highlighting the efficacy of the SAS method in enhancing early reading skills among primary students. These findings provide valuable insights for educators and policymakers to improve literacy rates through evidence-based instructional strategies.